2015
DOI: 10.1074/jbc.m115.638205
|View full text |Cite
|
Sign up to set email alerts
|

Dual Exosite-binding Inhibitors of Insulin-degrading Enzyme Challenge Its Role as the Primary Mediator of Insulin Clearance in Vivo

Abstract: Background: Insulin-degrading enzyme (IDE) is the best characterized catabolic enzyme implicated in insulin proteolysis. Results: Newly discovered dual exosite IDE inhibitors do not significantly affect insulin action or clearance. Conclusion: IDE catabolism does not appear to be the primary mechanism of insulin clearance in vivo. Significance: These IDE inhibitors will enable broader investigation of IDE function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(76 citation statements)
references
References 43 publications
4
72
0
Order By: Relevance
“…In turn, using a structurebased approach, Durham et al designed a series of novel dual exosite-binding IDE inhibitors which do not interact with the catalytic zinc of the protease (50). However, as published in the literature, only two of abovementioned IDE inhibitors were tested in vivo and demonstrated stability, pharmacokinetic properties and physiological effects, thus confirming their potential for the development of antidiabetic drugs (47,50). The results of these studies are described in detail below.…”
Section: Development Of Chemical Modulators Of Ide Activitymentioning
confidence: 74%
See 1 more Smart Citation
“…In turn, using a structurebased approach, Durham et al designed a series of novel dual exosite-binding IDE inhibitors which do not interact with the catalytic zinc of the protease (50). However, as published in the literature, only two of abovementioned IDE inhibitors were tested in vivo and demonstrated stability, pharmacokinetic properties and physiological effects, thus confirming their potential for the development of antidiabetic drugs (47,50). The results of these studies are described in detail below.…”
Section: Development Of Chemical Modulators Of Ide Activitymentioning
confidence: 74%
“…Further, prolonged IDE inhibition may lead to amyloid deposition and cytotoxicity in pancreatic beta-cells (46) (Figure 1). Paradoxically, Durham et al found no action of another (dual-exosite) IDE inhibitor NTE-1 on insulin and glucagon degradation in vivo, although it resulted in elevated plasma amylin levels and improved glucose excursion in oral glucose tolerance test (50). Authors hypothesized that these contradictory findings may be explained by differences in biochemical mechanisms of action or biodistribution of 6bK and NTE-1, but further experimentation is needed to clarify this.…”
Section: Compoundmentioning
confidence: 91%
“…However, Durham et al (10) found that an IDE inhibitor did not increase plasma insulin levels or improve insulin sensitization, and concluded that IDE plays only a limited role in insulin clearance. Moreover, Steneberg et al (9) reported that IDE knockout mice did not exhibit elevated fasting insulin levels, in contrast to other findings.…”
Section: Ide Localization To Endosomes Involves the Polyanion-bindingmentioning
confidence: 99%
“…Evidence supporting a role for IDE in degrading insulin and Aβ in vivo includes associations of IDE gene variants with type 2 diabetes (1, 2) and Alzheimer's disease (3,4), decreased clearance of the two peptides in IDE-deficient mice (5,6), and antidiabetic activity produced by IDE inhibitors (7,8), although some reports have questioned its role in insulin degradation (9,10). In addition, IDE has been reported to have noncatalytic functions, such as acting as a receptor for varicella-zoster virus (11) and serving as a heat shock protein in stressed cells (12).…”
mentioning
confidence: 99%
“…Recently, a novel class of IDE inhibitors was discovered, but these compounds do not interact with the catalytic zinc of the protease. Instead, the inhibitors bind to the dual exosite of IDE (57). The co-crystallization of the N-terminal tag acting as a pseudo-substrate with PqqF provides a novel idea for future designs of IDE inhibitors.…”
Section: D-glucose-mediated Inhibition Of Prodigiosin Production-mentioning
confidence: 99%